PERBEDAAN KEMAMPUAN MATEMATIKA CALON MAHASISWA BARU UNIVERSITAS ASAHAN BERDASARKAN JENIS KELAMIN - Sitorus, Zuriah (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The researchaimed to determine thedifferences intest resultsof matriculants of Asahan University that were based on gender. To achievethese objectives, the research took samplesby genderandschoolof origin. The results of hypothesis testingshowed that women matriculants hadbetter testresultsthanthemen. This wasevidencedbytcount=2.76>ttable =2.01at significance levelÎ±=0.05. Â  Kata Kunci :jenis kelamin, tes matematika